John and Elaine Steinbeck with Mimi Guercin in Fez, Morocco (2022)
John and Elaine Steinbeck, with Mimi Guercin, in the Fez Souk. Fez, Morocco, is the oldest city in Africa and Fez Souk is one of the oldest marketplaces. Souks are the traditional marketplaces and are found in the medinas, the oldest, walled section of a city. Original in safe